Projeto e favela: metodologia para projetos de urbanização - Bueno, Laura Machado de Mello (Universidade de São Paulo. Faculdade de Arquitetura e Urbanismo., 2000)
This work presents a phd thesis about a methodological proposal for the improvement of projects and works for up-grading urban conditions of favelas in Brasil. The illegal settlement phenomenon is posed as one of the housing alternatives of the poor population of many peripheral countries, even the understood, including Brazil, among the emergent. Official policies on favelas in Brazil are centred to this thesis which also studies the origins and the growth of favelas, the development of relevant public policies and the access of favela dwellers to public services, as rights, within a case history of the São Paulo municipality. The historically and socially constructed transformation, of public policies and projects developed for favelas are presented, in the context of Brazilian experience, specially São Paulo e Rio de Janeiro. The process of the development of methods of intervention and paradigms of urban settlement and design are considered, since 1940. Study cases on appraisal of urbanization works of favelas, in terms of build projects, are presented, based on coletive empirical research developed in 1999. The social, urban and environmental adequacy of favela programmes is discussed. On the basis of research findings, the question of the landscape aesthetics of urbanized favelas is also discussed, focusing on the specific spacial qualities resulting from the design solutions. The central focus of the thesis is a contribution for the improvement of projects and construction in favelas, as a social and spatial wideness of the response to one of glaring inequities of Brazilian urbanization